The Role of Corporate Governance in Moderating the Influence of Corporate Social Responsibility Disclosure, Investment Risk and Firm performance in Manufacturing Companies Listed on the Indonesian Stock Exchange 2018-2022 - Baety Nur Rohmah; Erma Setiawati; Rina Trisnawati (Journal Research of Social Science, Economics, and Management, 2023)
Purpose: This study aims to analyze the impact of Corporate Social Responsibility Disclosure (CSRD) and investment risk on firm performance with CEO integrity, ownership concentration, and independent board as moderating variables. CEO integrity, concentrated ownership, and an independent board of directors are hallmarks of Good Corporate Governance (GCG). Methodology: This study uses manufacturing companies listed on the Indonesia Stock Exchange during the period 2018-2022. The total sample for this study included 107 dates. Purposive sampling technique was used for the sampling method and SPSS 24 software was used for data processing in this study. Results: The results of in this research show that CSR disclosure does not have a significant impact on firm performance. Investment risk has a positive and significant impact on a company's performance. CEO integrity does not moderate the effect of his CSR disclosure on firm performance, but ownership concentration and independent board of directors moderate the effect of her CSR disclosure on firm performance. Although CEO and independent board integrity do not moderate the effect of investment risk on firm performance, ownership concentration does moderate the effect of investment risk on firm performance. Applications/Originality/Value: Even if an organization makes CSR disclosures, it does not directly impact its financial performance. Companies must understand and carefully manage investment risk to maintain and improve performance. Additionally, this study shows how ownership concentration and independent boards moderate the impact of CSR disclosure, it shows that highlighting the importance of corporate structure in optimizing corporate sustainability impact.